Effect of Firing Holding Time on Density, Porosity, and Hardness, Crucible Materials Based on Evaporation Boats - Hidayat, Wakhid Muhlisin; Rusiyanto, Rusiyanto; Widodo, Rahmat Doni; Sumbodo, Wirawan; Fitriyana, Deni Fajar (International Journal of Mechanical Engineering Technologies and Applications, 2022)
Evaporation boats are conductive advanced ceramic composites with the best thermal evaporation source for metalizing applications. The short life time of the evaporation boats causes the metalizing industry to produce large amounts of evaporation boats waste. However, studies on the utilization of evaporation boat waste are still limited. Therefore, this study aims to determine the effect of firing holding time on the density, porosity, and hardness of crucible materials made from evaporation boats waste. The material used in this research is a mixture of evaporation boats waste powder, kaolin, and graphite, with a composition of 50%, 25% and 25%, respectively. During the mixing process, 15% of the water is added. The compacting process carried out with a compaction pressure of 25 MPa. The firing process is carried out at a temperature of 1000oC with holding times of 60, 90, 120, 150, and 180 minutes. The test results show that the holding time of firing has an effect on density, porosity, and hardness. The highest density value was 1,91 g/cm3 at a holding time of 180 minutes, and the lowest was 1,77 g/cm3 at a holding time of 60 minutes. The highest porosity value is 4,10% at a holding time of 60 minutes, and the lowest is 2,16% at a holding time of 180 minutes. The highest hardness value was 12,84 HV at a holding time of 180 minutes, and the lowest was 8,3 HV at a holding time of 60 minutes. The longer holding time in the firing process results in a decrease in the porosity content. The decrease in the porosity content results in an increase in density and hardness of the cruicible specimens.